Acompañamiento de los padres de familia en casa y la creatividad en los niños de cinco años de la Institución Educativa Inicial N° 172 Ángel de la Guarda, Iquitos 2021 - Sajami Puerta, Jhuleyssy (2022)
This research has been developed with the purpose of relating the accompaniment of parents at home and creativity in five-year-old children of the Initial Educational Institution No. 172 "Guardian Angel" Iquitos 2021. The research is relational, with a cross-sectional field design. The population considered was 50 initial level students, while the sample was census. Observation and interview were used as a technique, questionnaire as an instrument to obtain the data, previously the instruments were validated through expert judgment. The conclusion is that there is a significant relationship between the accompaniment of parents and the creativity of five-year-old children of the Initial Educational Institution No. 172- "Guardian Angel" Iquitos 2021.